RESEARCH OF INNOVATIVE FORMS` PRACTICAL CLASSES REALIZATION IN CONDITION OF EUROPEAN CREDIT TRANSFER SYSTEM OF STUDYING AND REFORMATION OF HIGH SCHOOL - Рожко, М. М.; Ерстенюк, А. М.; Попович, Ю. І.; Іванців, М. О.; Кобрин, Т. З. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The article is devoted to generalization of monitoring commission connected with a quality of practical classes in IFNMU with a purpose of department experience studying in providing of master classes, public classes, search for innovative forms in practical classes` practice in condition of high school reformation and providing europian credit-transfer system and experience expanding on other departments.